Production Planning and Operational Cost Management of Manufacturing Firms in Rivers State (Texas Journal of Multidisciplinary Studies, 2023)
his paper investigates the critical interplay between production planning and operational cost management within the manufacturing firms of Rivers State, Nigeria. The study delves into the complex relationships between these two essential facets of business operations, shedding light on how they impact the competitiveness and sustainability of manufacturing enterprises in this region. Employing a quantitative research design, data were collected from three prominent manufacturing firms, namely Demcok Paints, Glaxo Paint Nigeria Limited and Terra Paint through a convenient sampling method. The analysis reveals intriguing insights into the connections between market demand analysis, quality control, labor productivity, regulatory compliance, and their impact on operational costs and production efficiency. The findings of this study have the potential to guide manufacturing firms in Rivers State toward more effective strategies for optimizing production planning and cost management, thereby enhancing their competitiveness and longterm viability.